Work Safety Procedures In Loading /Unloading Activities at PT. Buana Lintas Lautan Tbk Batam Branch - Dewa Surya Dinata; Yuna Sutria; Fadiyah Hani Sabila (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study was conducted with the aim of finding out how the work safety procedures are in loading/unloading activities at PT. Buana Lintas Lautan Tbk, Batam Branch. The author obtained data using field research methods and library research methods. The company PT. Buana Lintas Lautan Tbk, Batam Branch is a freight forwarding service company engaged in loading/unloading activities. In loading/unloading work, it is closely related to work that can cause work accidents, whatever the work that moves, is stored and transported, has many risks. Work safety procedures in loading/unloading activities at PT. Buana Lintas Lautan Tbk, Batam Branch have been running well. This is done for the good of the company and loading/unloading workers. To ensure the safety and health of workers in carrying out loading/unloading work, work safety procedures are implemented so that all workers feel safe and comfortable in carrying out their work, although there are still workers who do not use personal protective equipment in the loading/unloading process.